IMPLEMENTASI KAIDAH al-Mashaqat Tajlib al-Taisir ATAS TRANSAKSI E-COMMERCY SELAMA MASA PANDEMIC COVID-19 - achmad fageh (Education for Islamic Studies Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2021)
The implementation of e-commerce transactions in the covid-19 pandemic condition seen from the perspective of Jurisprudence of rules tends to be close to the third basic rule of al-Mashaqat Tajlib al-Taisir. This rule means difficulty in bringing convenience, meaning that when people are in a difficult situation in meeting their needs because of largescale social restrictions (PSBB), transacting using online marketplaces can be one of the convenient solutions. Among the nine branches of the rule, there are at least three significant rules with the application of e-commerce transactions in the covid19 pandemic condition. The first rule is